Agricultural Battalions to Enhance National Defense Food Security Under Policy Establishment of 500 Units - Mayyasari T. Gondokusumo; Robby M. Taufik (Reviu Akuntansi, Manajemen, dan Bisnis, 2026)
Purpose: This study analyzes the establishment of 500 Agricultural Battalions (YON TP) as a response to non-traditional food security threats in Indonesia and its role in strengthening national defense under VUCA conditions.Research Methodology: This study uses a qualitative document-based policy analysis using official regulations, ministerial reports, and inter-agency agreements.Results: Results show that YON TP can strengthen the four FAO pillars of food security through production, distribution, and training functions, but effectiveness depends on governance clarity and peace–war context differentiation.Conclusions: Military involvement in food systems may create dual-function risks if civilian oversight is weak, while comparative cases show success depends on farmer empowerment, decentralization, and agroecological approaches.Limitations: This study is limited to qualitative document analysis without field validation or quantitative measurement of program performance. Contribution: This study contributes by integrating FAO food security framework with VUCA and hybrid threat perspectives to analyze the role of Agricultural Battalions (YON TP) in strengthening Indonesia’s food security under complex governance conditions. Practically, it offers policy insights on the importance of governance clarity, civilian oversight, and farmer empowerment to ensure that military involvement in food systems remains effective, sustainable, and aligned with national resilience goals.